1949
DOI: 10.1042/bj0450051
|View full text |Cite
|
Sign up to set email alerts
|

Properties of the acid phosphatases of erythrocytes and of the human prostate gland

Abstract: There is much evidence indicating the non-identity of acid phosphatases of different origin. Davies (1934) has shown that the acid phosphatase of the red cell differs from that of spleen in that the former hydrolyses x-glycerophosphate much more readily than the ,-compound, while with the spleen enzyme ,-glycerophosphate is hydrolysed more quickly. Kutscher & Worner (1936) described the irreversible inactivation of the prostatic acid phosphatase by certain narcotics, including alcohols. This was used by Herber… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
45
0
3

Year Published

1954
1954
2003
2003

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 262 publications
(53 citation statements)
references
References 9 publications
5
45
0
3
Order By: Relevance
“…The phosphate esters 4a and 4b must undergo a chemical or enzymatic bioconversion to release the parent drug in order to fulfill the prodrug criteria. In addition to red blood cells 27 alkaline phosphatases have been found in various human tissues; e.g., placenta, intestine, liver, bone, and kidney, 28 and they have been reported to be the responsible enzymes for the hydrolysis of phosphate esters. 16,29 The susceptibility of buparvaquone phosphate esters (4a,b) to enzymatic hydrolysis was studied in alkaline phosphatase enzyme solution (Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…The phosphate esters 4a and 4b must undergo a chemical or enzymatic bioconversion to release the parent drug in order to fulfill the prodrug criteria. In addition to red blood cells 27 alkaline phosphatases have been found in various human tissues; e.g., placenta, intestine, liver, bone, and kidney, 28 and they have been reported to be the responsible enzymes for the hydrolysis of phosphate esters. 16,29 The susceptibility of buparvaquone phosphate esters (4a,b) to enzymatic hydrolysis was studied in alkaline phosphatase enzyme solution (Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…In these respects, it behaves like the enzyme in normal serum (18,19). Others have shown that L-tartrate inhibits acid phosphatase from prostate, liver and spleen, but not the normal serum enzyme (18).…”
Section: Discussionmentioning
confidence: 99%
“…The Acid-phosphatase activity was assessed at pH 4-9 (citrate) by the method described by Bell & Siller (1962) (Mann, 1954). Human prostatic acid phosphatase shows properties towards certain inhibitory substances that distinguish it from acid phosphatases from other sources (see Abul-Fadl & King, 1949). The effects of Ca2+, Cu2+, Mg2+, F~, and dextrorotatory tartrate on the acid-phosphatase activity of cock seminal-plasma acid phosphatase have already been reported (Bell & Lake, 1960, 1962 The results of the boar analyses show that the bulk of the alkaline phos¬ phatase accompanies the first or spermatozoon-rich wave of ejaculation.…”
Section: Introductionmentioning
confidence: 99%